Zero sum - Gilstrap, John (Gilstrap, John. Jonathan Grave thriller., 2024)
Jonathan Grave long ago lost faith with the so-called war on drugs, a futile campaign that enables cartels to make billions under the protection of corrupt officials on both sides of the border. But when a twelve-year-old dies after consuming fentanyl disguised as candy inside the dormitory at Resurrection House, the school he created for the children of incarcerated parents, Jonathan knows it's time to use his special talents to change the game. Gathering his Security Solutions team, Jonathan activates Operation Heat Seeker. Nobody and nothing will stop them from ending the flow of poisonnot even a vow of revenge from the President of the United States himself . . .